Colurostylis castlepointensis, a new shallow-water diastylid (Crustacea: Cumacea) from New Zealand - Gerken, Sarah; Lörz, Anne-Nina (Zootaxa, 2007)
Colurostylis castlepointensis sp. nov. is described from Castle Point, New Zealand. Colurostylis castlepointensis can be differentiated from all known species of Colurostylis by the combination of a smooth anterolateral angle on the carapace, carapace without ridges, uropod peduncles longer than pleonites 5 and 6 together, and uropod exopod longer than endopod.  A key to all species of Colurostylis is included